Food Purchase by Islamic Youth: When Buying and Selling Contracts and Halal Awareness Ignore by Taste - Marlya Fatira AK; Asmuni Asmuni; Tuti Anggraini; Suraya binti Abd. Warif (Forum Kerjasama Pendidikan Tinggi, 2023)
This study conveys an overview of the purchasing decisions made by the younger generation of Muslims in buying trending food and its relation to ignoring sales, purchase contracts, and halal product information. The type of research used in this research is quantitative research. They are collecting research data using a questionnaire or questionnaire. The respondents of this study were 130 Muslim students at Medan State Polytechnic. The Data analysis techniques use descriptive statistics with quantitative descriptive methods. The questionnaire method operates as a source for data collection. The style used is the distribution of frequency tables by displaying the frequency and percentage of the results of the respondents, which are processed using the Microsoft Excel program. The results showed that the younger generation of Muslims, represented by Muslim students at the Medan State Polytechnic, tended to purchase trending foods, in this case, Mie Gacoan, based on their taste for the product and the various variations of Mie Gacoan products offered in restaurants. Sales and purchase contracts and information on the halal food products restaurants offer are sufficient as a reference. However, they are not the primary determinant in purchasing food products. This condition takes a clear picture that in the era of openness and digital like today, buying and selling contracts in service at restaurants are still things that need to be displayed by restaurants so that they can be a reference for consumers in deciding to purchase products, even though the form of the contract is not signed between the consumer and the restaurant owner. Such as a sale and purchase contract, but special conditions or small agreements that are displayed, such as refund conditions or meal replacement policies submitted by the restaurant in writing, become a form of restaurant service initiative to consumers so that these conditions can provide a framework for relationships between customers and restaurants. In the Islamic view, the contract for food in a restaurant can refer to the principles of Islamic law or sharia. These principles include Halal Compliance, Food Quality, Fairness in Transactions, Obligation of Information, Service, and Ethics. In Islamic law, adherence to the above principles is essential to maintaining fairness, integrity, and consumer welfare. But in the end, it is still the consumer who determines the decision to buy or not a product according to this contract, that currently the priority is the basis for consumer thinking to decide to buy more because of the urge of taste. The illustrated in the buying decision of Mie Gacoan by the younger generation of Islam at Medan State Polytechnic